EPISTEMOLOGI FIQH SABILAL MUHTADIN - Pancasilwati, Abnan (IAIN Samarinda, 2015)
This article analyses Sabilal Muhtadin, a magnum opus of Syekh Muhammad Arsyad al-Banjari in Islamic jurisprudence. Al-Banjari is considered as a prominent intellectual from Banjarmasin, Indonesia who could contribute to the development of Islamic law beyond the municipal and national territory. In writing the Sabilal Muhtadin, al-Banjari have used three models of ijtihad, namely deductive, inductive, and the combination of the two. In applying the deductive method which should only refer to the verses of the Qur’an or the Hadith, however, he extends it to the opinion of previous Islamic jurits. This then proves that al-Banjari is not an independent mujtahid who exercise free ijtihad like the eponyms of Islamic schools of law. Yet, by applying the inductive (especially, maslahah and sadd adz-dzari’a) and the combined deductive-inductive methods, he is able to accommodate the social changes to the requirements of shari’a. Sabilal Muhtadin thus mirrors the intellectual developments within Islam responsive to the author’s circumstances.